Going global? : U.S. government policy and the defense aerospace industry - Lorell, Mark A., 1947- (RAND, Project Air Force, 2002)
Since the end of the Cold War, a dramatic decline in overall defense authorizations has led both the U.S. aerospace industry and that of Europe to undergo extensive consolidation -- a trend that has led in turn to a significant growth in cross-border business relationships. Yet while globalization has the potential to increase competition, foster innovation, encourage fair pricing, and promote interoperability among NATO allies, it also poses potential challenges, particularly with regard to the proliferation of advanced U.S.-developed military technologies.